2022
DOI: 10.1242/dev.200330
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Prm1 leads to defective chromatin protamination, impaired PRM2 processing, reduced sperm motility and subfertility in male mice

Abstract: One of the key events during spermiogenesis is the hypercondensation of chromatin by substitution of the majority of histones by protamines. In humans and mice, protamine 1 (PRM1/Prm1) and protamine 2 (PRM2/Prm2) are expressed in a species-specific ratio. Using CRISPR-Cas9-mediated gene editing, we generated Prm1-deficient mice and demonstrated that Prm1+/− mice were subfertile, whereas Prm1−/− mice were infertile. Prm1−/− and Prm2−/− sperm showed high levels of reactive oxygen species-mediated DNA damage and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…Of note, a recent study investigating a single residue mutation in PRM1 showed increased histone retention, but no disturbances in transition protein retention in such mice [ 46 ]. In Prm1 -/- transition protein retention is also present, albeit weaker than seen here [ 38 ]. Transition proteins are believed to aid in chromatin condensation by stabilizing the DNA in a non-supercoiled state, cooperating with topoisomerases to relieve torsional stress and to be involved in DNA repair during chromatin condensation [ 53 – 55 ].…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Of note, a recent study investigating a single residue mutation in PRM1 showed increased histone retention, but no disturbances in transition protein retention in such mice [ 46 ]. In Prm1 -/- transition protein retention is also present, albeit weaker than seen here [ 38 ]. Transition proteins are believed to aid in chromatin condensation by stabilizing the DNA in a non-supercoiled state, cooperating with topoisomerases to relieve torsional stress and to be involved in DNA repair during chromatin condensation [ 53 – 55 ].…”
Section: Discussionmentioning
confidence: 47%
“…While in WT condensed spermatids unprocessed PRM2 seems to accumulate in cytoplasm and residual bodies in Prm2 +/Δc mice it is detected in the nucleus and does not seem to be evicted into the cytoplasm. Incomplete PRM2 processing has been reported in several mouse models of genes involved in the histone-to-protamine transition, such as transition proteins, PRM1 and H2A.L.2 [ 8 , 21 , 23 , 38 , 46 , 52 ]. At least in this study, however, it seems that rather than failure of complete processing of PRM2 we see a failure of eviction of unprocessed PRM2 into the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The essentiality of both protamines for sperm chromatin rearrangement is evident from the extensive investigation using mouse models (Cho et al 2001, Mashiko et al 2013, Takeda et al 2016, Schneider et al 2020, Arévalo et al 2022, Merges et al 2022). However, it is still unclear why two protamines are required in some species whereas one protamine (PRM1) appears to be sufficient in others.…”
Section: The Protamine Ratiomentioning
confidence: 99%
“…Over the last two decades, several protamine-deficient mouse models have been generated using a variety of different approaches (Cho et al 2001, Mashiko et al 2013, Takeda et al 2016, Schneider et al 2020, Arévalo et al 2022, Merges et al 2022 (Cho et al 2001(Cho et al , 2003. Using homologous recombination, they generated Prm1 +/− and Prm2 +/− embryonic stem (ES) cells, which upon blastocyst injection produced several male and female chimeras.…”
Section: Protamine-deficient Mouse Modelsmentioning
confidence: 99%